Driving Behavior of Online Ojek X towards Safety Driving in Anggana Sub-district - Ayyik Busromaqoli; Nina Mardiana; Dian Ardiyanti (Jurnal Kesehatan Masyarakat Indonesia (JKMI), 2024)
Abstract Traffic accidents in East Kalimantan, particularly in Anggana District, pose a serious issue. As of October 2023, there have been over 20 cases of minor to moderate accidents involving online motorcycle taxi drivers, often due to the negligence of other road users. This study employs a qualitative method with a case study design, involving 9 informants. Results indicate that the use of Personal Protective Equipment (PPE) by Ojek Online X is rated positively by passengers. Drivers who are healthy and well-rested are motivated by attractive earnings and flexible schedules. Ojek Online X prioritizes quality service through vehicle maintenance to reduce accident risks. A safe working environment is crucial for maintaining a positive public image. In conclusion, good PPE usage, adequate rest, and financial motivation contribute to safety and work quality. These findings can serve as a reference for other online motorcycle taxi drivers in implementing Safety Riding principles.